Performance Analysis, Self-Concept, and Motivation of Physical Education Teachers at SMPN Sungai Lilin Subdistrict, Musi Banyuasin Regency - Defita, Jeni; Hartono, Mugio; Nasuka, Nasuka (Journal of Physical Education and Sports, 2021)
Becoming a professional teacher can be seen from how their performance, self-concept, and motivation carry out their duties and responsibilities in teaching. This study aims to obtain a description of the performance analysis, self-concept, motivation of physical education teachers at SMPN in Sungai Lilin Subdistrict, Musi Banyuasin Regency. This type of research uses exploratory research. The sources of the research were obtained directly from physical education teachers, school principals, and colleagues through observation, interviews, and documentation. The data analysis technique used was the SWOT analysis technique with a qualitative approach. The results of the study explained that PJOK teachers who have a good quality of performance abilities had completed the learning program appropriately. The self-concept of the PJOK teacher by becoming a teacher is his goal, to be positive in responding to unpleasant experiences. Physical education teacher motivation based on internal and external motivational factors is built with the support of all parties. The conclusion of the study shows, the results of the performance of PJOK SMPN teachers in Sungai Lilin Subdistrict, Musi Banyuasin Regency, are said to be able to carry out their duties and responsibilities well. The self-concept of PJOK teachers is said to be good if it is proven that being a teacher is his ideal. And can positively respond to unpleasant experiences. The motivation of PJOK teachers based on internal and external factors shows that motivation is fairly good with the appreciation given.